Konsensus Setengah Hati: Perjalanan Peradilan Agama Menuju Sistem Satu Atap (1999-2004) - Dian Kurnia Hayati (Jurnal Hukum Lex Generalis, 2021)
During the Reformation era, Islamic law had space in public. This was also strengthened by state policies to reform various aspects of life, including the field of law. The legal reform agenda provides room for strengthening Islamic law institutionally through the Religious Courts. In this case, the Religious Courts are to be integrated under the Supreme Court to end the dualism of guidance and dual supervision between the Supreme Court and the Ministry of Religion. In this study, the authors discuss the differences in views between the Religious Courts, the Ministry of Religion, and the Supreme Court in the process of integrating the Religious Courts under one roof. The method used is the historical method with a statutory approach. The main source used is the primary archive in the form of trial minutes of the Draft Law No. 35/1999 concerning Judicial Power, Draft Law No. 4/2004 on Judicial Power, magazines, and contemporary newspapers. The new findings in this article are the pros and cons of the integration process of the Religious Courts due to differences in interests among stakeholders. Thus, it is concluded that the factors of integration of the Religious Courts are not limited to the ideal basis for realizing judicial independence within the framework of reform, but are closely related to economic and political aspects.